2017
DOI: 10.1097/md.0000000000005290
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and the risk of low bone mass–related fractures in women compared with men

Abstract: Background:Body mass index (BMI) is inconsistently associated with the progression of low bone mass–related fractures. We conducted a systematic review and meta-analysis to summarize the evidence regarding the relationship between BMI and the risk of fracture in men and women separately. Furthermore, we analyzed the association between BMI and fracture risk in women compared with men.Methods:PubMed, EmBase, and the Cochrane Library were searched up to November 2015 to identify prospective cohort studies of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 52 publications
(70 reference statements)
1
14
0
1
Order By: Relevance
“…all traits known to increase in individuals with higher BMI [26][27][28][29] . The extent to which these secondary phenotypes reflect causal associations between genetic risk and disease is unclear due to the commonality of co-morbidity of these traits.…”
Section: Discussionmentioning
confidence: 99%
“…all traits known to increase in individuals with higher BMI [26][27][28][29] . The extent to which these secondary phenotypes reflect causal associations between genetic risk and disease is unclear due to the commonality of co-morbidity of these traits.…”
Section: Discussionmentioning
confidence: 99%
“…In osteoporosis research, animal models have been used for more than a century and have helped to elucidate the underlying disease mechanisms and explore new targets for treatment. Since several risk factors have been associated with osteoporosis like age [22], menopausal status [23], hormonal dysregulation [24], malabsorption [25], side effects to medication like prednisolone [26], smoking [27], low BMI [28], immobilization [29], and disuse [30], it is crucial to select the appropriate animal model. Previous studies have revealed that the magnitude of bone loss varies between the different models used [7,11,31].…”
Section: Discussionmentioning
confidence: 99%
“…This may be the reason for the insignificant effects of healthy behaviors on WC and other MRFs in the underweight subgroup. Nevertheless, underweight individuals have been found to be associated with a high risk of health-related problems such as osteoporosis, infection, and decreased immune function [ 59 , 60 ]. Therefore, the needs of workplace health promotion for underweight individuals should be targeted in different ways.…”
Section: Discussionmentioning
confidence: 99%